Foreground selection through SSRs markers for the development of salt tolerant rice variety (Journal of the Bangladesh Agricultural University, 2014)
Salinity is a great problem for rice production worldwide incurring substantial yield loss; a great threat towards food security. Marker-assisted backcrossing is one of the feasible methods to develop a new salt tolerant rice cultivar to cope with the challenge. The study was focused on to introgress salt tolerant genes from a tolerant rice line, FL-478 to Binadhan-7, an early, agronomically suitable and susceptible variety. Backcrossing was done during boro season; where Binadhan-7 was the recurrent parent and FL-478 was the donor parent. 141 BC1F1 lines were developed, which were subjected to foreground selection; the first level of selection of marker assisted backcrossing program. The aim of foreground selection was to identify the introgressed lines. 141 BC1F1 populations were evaluated with tightly linked salt tolerant markers; AP3206f, RM3412b and RM336. A total of 47 heterozygous BC1F1 lines were selected finally, which have alleles of both of the parents. Those introgressed lines could be efficiently used in further development of a stable early salt tolerant rice variety. DOI: http://dx.doi.org/10.3329/jbau.v11i1.18215 J. Bangladesh Agril. Univ. 11(1): 67-72, 2013